Kompetensi Kepala Sekolah Sebagai Leader Dalam Meningkatkan Pendidikan Mutu Pendidikan Agama Islam di Sekolah Dasar Al-Ma’arif 02 Singosari Malang - Bakri, Maskuri; Hosna, Rofiatul (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
This study aims to describe, personality, understanding of vision and mission, decision-making systems, and communication of school principals as leaders in improving the quality of Islamic education in schools. This study uses a qualitative approach to the type of case studies, the analysis uses Milles and Huberman's analysis techniques. The result is an increase in the quality of Islamic Religious Education (PAI) very closely related to the competency capabilities of the principal as a leader. At SDI Al-Ma'arif 02 proves that the school principal is currently able to improve the quality of PAI because they have good leader competencies, namely, personalities based on Islamic values ​​competencies, decision-making abilities that satisfy all parties, understanding the development of vision, mission and strategic goals PAI learning and institutional as well as the implementation of quality improvement programs for PAI teachers. This competency can be seen from the ability of SDI Al-Ma'arif 02 to produce graduates who have high religious quality and establish synergy between institutions and the community.